2009
DOI: 10.1086/598242
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Incidence Study of Bloodstream Infection in Infants and Children With Central Venous Catheters After Cardiac Surgery in Italy

Abstract: This prospective observational study was designed to assess the incidence of, risk factors for, and outcome of catheter-related bloodstream infection in children undergoing cardiac surgery. A staff specifically trained to handle the central venous catheters with proper aseptic techniques and an appropriate patient to medical staff ratio remain the most effective measures to prevent this infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…Comparisons between umbilical catheters, PICCs, tunneled CVADs, and nontunneled CVADs based on dwell time, occlusion, thrombosis, and infection risk were the primary focus of the included studies. 15,31,35,88 Generally, short-term peripheral and nonperipheral compatible therapy delivered via umbilical catheters in infants can be used. 66 PICCs were recommended for patients with congenital cardiac conditions requiring $7 days of IV therapy.…”
Section: Congenital Cardiac Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons between umbilical catheters, PICCs, tunneled CVADs, and nontunneled CVADs based on dwell time, occlusion, thrombosis, and infection risk were the primary focus of the included studies. 15,31,35,88 Generally, short-term peripheral and nonperipheral compatible therapy delivered via umbilical catheters in infants can be used. 66 PICCs were recommended for patients with congenital cardiac conditions requiring $7 days of IV therapy.…”
Section: Congenital Cardiac Conditionsmentioning
confidence: 99%
“…136 CVAD (tunneled and nontunneled) use was reported in this population; however, placement $7 days was associated with an increased risk of CLABSI. 31,56 None of the included studies or guidelines included evidence to support the use of totally implantable venous devices in this population.…”
Section: Congenital Cardiac Conditionsmentioning
confidence: 99%
“…These data also were not included in the review. We were unable to ascertain the number of catheter days in 23 studies, [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]84,85,92,97,99,122 which excluded their data from contributing to the meta-analysis reporting failure and complications per 1000 catheter days. Because of a lack of data, the rate of CVAD failure per 1000 catheter days for nontunneled, percutaneous CVADs could not be estimated.…”
Section: Study Qualitiesmentioning
confidence: 99%
“…A study done in Naples on 120 oncologic children found a positivity of blood cultures from central line in about one third (28.3%; 128/425 samples) of cases clinically suspected for infection [11]. There are two prospective studies performed in Turin: the first included 748 oncologic or immunologic patients within 7 years, registering 174 episodes of CLABSI [12], whereas the second enrolled 153 children with previous cardio-surgery, founding a CLABSI incidence of 11.7/1000 central line-days [13]. The only point-prevalence survey available in the Italian pediatric population was set in a large tertiary care children’s hospital in Rome between 2007 and 2010.…”
Section: Introductionmentioning
confidence: 99%